PENGEMBANGAN INSTRUMEN EVALUASI OTENTIK BERBASIS HOTS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP DARUL HUDA BANYUWANGI - Muhammad Arif Zaenal Abidin Muhammad Arif Zaenal Abidin; Ahmad Fathi Naufal Hasby (Lembaga Sepercenter, 2026)
The evaluation of Islamic Religious Education (IRE) in schools often focuses solely on the cognitive aspects of low-level thinking (LOTS), failing to measure students' spiritual and social competencies holistically. This research aims to develop a Higher Order Thinking Skills (HOTS)-based authentic evaluation instrument for IRE subjects. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study involved 120 high school students as a sample. Data collection techniques included expert validation, questionnaires, and trials. The results show that the developed instrument—which integrates performance-based assessment, portfolios, and HOTS-standardized objective tests—is highly valid and reliable. This research contributes to providing a new framework for IRE teachers in measuring the internalization of religious values, not just rote memorization. The conclusion emphasizes that authentic evaluation can significantly improve the quality of IRE learning outcomes in accordance with the demands of the 21st-century curriculum.